Sistem Informasi Manajemen Restoran Berbasis Web Responsive (Studi Kasus pada Restoran Mesra Sukabumi) - Didik Indrayana; Prayoga Dwi Agung Wibisono (Institut Manajemen Wiyata Indonesia, 2019)
Food ordering system that exist in Restaurant Mesra still use the usual way, to make customer reservations come and then the waiters deliver the menu while the waiter is still manually writting customer’s orders using paper. After that the waiters deliver the customer's order to the kitchen and deliver to the customer who ordered the food, after that the customer pays to the cashier. This has an impact on the inaccuracies and delays in the ordering process. This happens because Mesra Restaurant has not implemented a computer-based system that can facilitate the ordering of the menu, and making sales reports. This research was conducted to make restaurant management information system at Mesra Restaurant to resolved these problems. The methodology used is the analysis and design of object-based systems with UML diagrams and website creation with PHP programming language. The final result of this research is the formation of a website of restaurant management information system at Mesra Restaurant in accordance with the description of system analysis and can meet the desire of consumers and the restaurant.